Radiation cooling composite material with decoupled hierarchical functions and preparation method and application thereof

CN122979828APending Publication Date: 2026-10-27CHENGDU XIAODU DI TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611274333.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但现有公开资料显示,透过率可查证的仅为“>70%”左右水平——这是韩国首尔大学联合MIT研究团队2026年发表于Energy & Environmental Science的权威成果的参考基准之一,其整车实测车厢温度降低最高达6.1℃,节能超20%

Benefits of technology

[0043](1)本发明的反射层采用高折射率材料与低折射率材料交替堆叠的啁啾梯度多层膜结构。现有技术中,金属(Ag)反射层的使用在行业中非常普遍,其在高温高湿条件下的腐蚀风险是长久以来的顽疾。据已发表研究,在60°C、90%相对湿度大气条件下仅老化1天,Ag薄膜即开始腐蚀,腐蚀产物主要为Ag2O。汽车窗膜长期暴露于高湿、盐雾、酸雨等恶劣室外环境,Ag层的氧化失效将导致窗膜反射率逐年衰减——呈现一种“新车三年膜效,五年透光率尚在但降温能力丧失”的渐进退化。本发明完全绕开金属反射层,以啁啾TiO2/SiO2全介质多层膜完成近红外反射任务——所有介质材料的禁带宽度均大于3.1eV,不存在光化学氧化或电化学腐蚀的热力学驱动力。在可预见的物理寿命内,不存在类似Ag层的退化问题。且该层在可见光波段不吸收、不反射(折射率差产生的干涉在可见光波段不构成反射条件)。到了近红外波段,TiO2/SiO2之间的折射率差(Δn≈1.0)使多光束干涉的周期性叠加建立光子带隙,近红外热辐射被牢牢阻挡在外,从而实现挡热不挡光。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979828A_ABST
    Figure CN122979828A_ABST
Patent Text Reader

Abstract

The application discloses a layered function decoupling radiative cooling composite material and a preparation method and application thereof. The composite material comprises a transparent substrate layer, a near-infrared chirp reflection layer, a gradient transition layer and a mid-infrared high-emission layer which are sequentially stacked. The near-infrared chirp reflection layer is a chirp multilayer film structure formed by alternately stacking high-refractive-index film layer materials and low-refractive-index film layer materials. The gradient transition layer comprises low-refractive-index film layer materials and high-refractive-index film layer materials, and the chemical components thereof continuously and gradually transition along the thickness direction. The mid-infrared high-emission layer comprises a transparent high-polymer material and a thermal radiation inorganic functional filler uniformly dispersed in the interior of the high-polymer material. The composite material has high visible light transmittance, high atmospheric window infrared emissivity and high-efficiency near-infrared reflection capability. The preparation method is simple and easy to implement, and the composite material can be mass-produced and widely applied to scenes with strict requirements on transparency and cooling performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of refrigeration thin film materials technology, specifically relating to a layered functionally decoupled radiation refrigeration composite material, its preparation method, and its application. Background Technology

[0002] Transparent radiative cooling materials are becoming one of the most fiercely contested areas in the global zero-energy cooling technology landscape. According to a KPMG industry report released in July 2025, the Chinese passive radiative cooling market is projected to grow at a CAGR of approximately 64%, reaching a scale of 3.2 billion yuan by 2030, with the building sector accounting for 53%. The global radiative cooling materials market is expected to approach 30 billion yuan, with a CAGR exceeding 13%. A definitive review published in Nano Energy in April 2026 precisely categorizes existing transparent radiative cooling technologies into three main types: intrinsically transparent, nanoparticle-reinforced, and micro / nanostructure photonic. This classification aptly summarizes the current technological landscape.

[0003] Each of the three types of solutions mentioned above has its own insurmountable physical limitations.

[0004] Intrinsically transparent materials directly utilize the infrared activity of polymer molecular bonds in the 8–13 μm atmospheric window, such as PDMS and PMMA, to achieve a natural unity of light transmission and emission. The Si–O bonds of PDMS and the C=O bonds of PMMA provide a natural emission platform through phonon resonance in the infrared band, enabling high transparency. However, the "ceiling" is also very obvious—relying solely on the molecular vibrations of the polymer itself, the infrared emissivity in the atmospheric window is difficult to exceed 0.85, and it is completely powerless in the near-infrared band, which accounts for about half of the total solar energy, resulting in a significant reduction in cooling effect.

[0005] Nanoparticle-reinforced polymers enhance infrared emissivity by introducing functional fillers such as silica (SiO2), titanium dioxide (TiO2), and zirconium oxide (ZrO2) into the polymer matrix, utilizing the phonon polarization resonance of inorganic particles. However, the difficulty of the "dispersion" process is severely underestimated. Nanoparticles readily aggregate in viscous polymer matrices—once micron-sized aggregates appear, they immediately scatter visible light, causing the film to appear white and haze to increase sharply. In the laboratory, this can be barely resolved using prolonged ultrasound and surface modification, but once scaled up to a mass production line, batch-to-batch haze fluctuations become a quality control disaster.

[0006] Micro- and nano-structured photonic systems can achieve "surgical" manipulation of incident spectra through subwavelength configurations such as one-dimensional photonic crystal multilayer films and three-dimensional ordered porous structures. In 2026, Professor Wang Cong and Professor Sun Ying's team at Beihang University published a simplified all-inorganic one-dimensional photonic crystal structure in ACS Applied Optical Materials, consisting of two periodically alternating SiO2 / Al2O3 layers, achieving high reflectivity of the solar spectrum and high emissivity of the atmospheric window. The spectral manipulation precision of this type of approach is impressive, but the cost is equally heavy—it relies on magnetron sputtering or electron beam evaporation for layer-by-layer deposition, requiring equipment investments of millions of yuan, with slow deposition speeds, difficulty in ensuring uniformity in large-area fabrication, and residual stress between film layers often leading to warping and cracking.

[0007] Furthermore, the current market trends of mainstream products warrant attention: Major global manufacturers of radiative cooling films include 3M, i2Cool, SPACE COOL, Radi-Cool, SkyCool Systems, Azure Era, and MG Energy, with the top five companies accounting for approximately 85.04% of global revenue in 2024. SkyCool Systems' patented film is a typical reflective solution—high solar reflectivity combined with high infrared emissivity—but its appearance is white or opaque, making it unsuitable for windows, sunroofs, and other light-transmitting applications. Azure Era's radiative cooling window film represents the forefront of the domestic transparent radiative cooling industry. Real-vehicle testing data shows that the film can reduce temperature by up to 12.7℃, with a continuous cooling power of up to 133W per square meter. However, publicly available data indicates that the verifiable transmittance is only around ≥70%—one of the benchmarks for authoritative findings published in Energy & Environmental Science in 2026 by a research team from Seoul National University and MIT, which showed a maximum reduction of 6.1℃ in the vehicle cabin temperature and energy savings exceeding 20%.

[0008] With the increasing demand for energy-saving and environmental protection technologies, the market urgently needs cooling film materials that can push visible light transmittance to over 88% while maintaining near-infrared reflectance ≥85% and atmospheric window emissivity ≥0.93. However, existing technologies cannot achieve these three indicators simultaneously on a single platform. Summary of the Invention

[0009] The purpose of this invention is to solve the above-mentioned problems and provide a layered functionally decoupled radiation cooling composite material, its preparation method and application. This composite material has high visible light transmittance, high atmospheric window infrared emissivity and efficient near-infrared reflectivity. Its preparation method is simple and easy to implement, can be mass-produced, and can be widely used in scenarios that have stringent requirements for both transparency and cooling performance.

[0010] To achieve the above objectives, on the one hand, the present invention provides a layered functionally decoupled radiation cooling composite material, comprising a transparent substrate layer, a near-infrared chirped reflective layer, a gradient transition layer, and a mid-infrared high emissivity layer stacked sequentially.

[0011] The near-infrared chirped reflective layer is a chirped multilayer film structure formed by alternating stacks of high-refractive-index film material A and low-refractive-index film material B, wherein the refractive index of the high-refractive-index film material A is n. A The refractive index of the low refractive index film material B is n. B ;

[0012] The gradient transition layer comprises a low-refractive-index film material B and a high-refractive-index film material C, with a continuous gradient in chemical composition along its thickness direction. The content ratio of the low-refractive-index film material B decreases, while the content ratio of the high-refractive-index film material C increases. The refractive index of the high-refractive-index film material C is n. C n B <n C <n A ;

[0013] The mid-infrared high-emissivity layer includes a transparent polymer material D and a thermally radiative inorganic functional filler uniformly dispersed within it. The gradient transition layer also includes a transparent polymer material D, which is uniformly doped into the terminal section of the gradient transition layer to form an organic-inorganic hybrid gradient terminal.

[0014] The near-infrared chirped reflective layer is used to form broadband reflection in the 780–2500 nm near-infrared band. The gradient transition layer is used to continuously transition the equivalent interface refractive index of the top surface of the near-infrared chirped reflective layer to the effective refractive index of the mid-infrared high-emissivity layer to eliminate interlayer interface Fresnel reflection loss. The mid-infrared high-emissivity layer is used to form broadband emission in the 8–13 μm atmospheric window.

[0015] This invention employs a layered functional decoupling design to address the contradictory physical mechanisms of three key functions: high visible light transmittance, high near-infrared reflectivity, and high mid-infrared emission. High refractive index differences favoring near-infrared reflection can cause interface reflection in the visible light band; phonon resonances favoring mid-infrared emission can lead to absorption tails on the short-wavelength side of the visible light spectrum. Based on this layered functional decoupling design, near-infrared reflection is achieved by a near-infrared chirped reflective layer, and mid-infrared emission is achieved by a mid-infrared high-emissivity layer. These two layers are optically "seamlessly welded" together by a gradient transition layer with a continuously varying refractive index. Any interface with abrupt refractive index changes will produce Fresnel reflection in the visible light band—even a difference of only 0.06 in refractive index results in approximately 0.04% reflection at each interface. Accumulated across multiple interfaces, this leads to a loss of several percentage points of visible light transmittance. The composite material designed in this invention, connected by a gradient transition layer, avoids abrupt interfaces between layers, instead creating a smooth transition region of refractive index—ensuring that visible light does not encounter significant refractive index "steps" throughout its path, thus suppressing reflection loss to near zero. This achieves high visible light transmittance, high atmospheric window infrared emissivity, and efficient near-infrared reflection capability.

[0016] In the aforementioned layered, functionally decoupled radiation-cooling composite material, the substrate layer serves as the physical support platform and the first light entry point for the entire composite material. The transparent substrate material can be any conventional material in the field; however, this invention preferably uses a substrate material with a transmittance ≥90% in the 400–780 nm visible light band, and further preferably, ultra-white float glass or optical-grade PET film.

[0017] In the aforementioned layered, functionally decoupled radiation-cooling composite material, the near-infrared chirped reflective layer serves as a "heat-blocking but not light-blocking" functional layer. It is a chirped gradient multilayer film structure composed of alternating high-refractive-index and low-refractive-index materials. Using a "high-refractive-index film layer / low-refractive-index film layer" as a basic periodic unit, preferably, the thickness of each single layer in the chirped multilayer film structure of the near-infrared chirped reflective layer decreases periodically along the direction away from the substrate, so that the Bragg reflection wavelength corresponding to the bottom period is in the long-wave near-infrared range while the Bragg reflection wavelength corresponding to the top period is in the short-wave near-infrared range. Under the condition of achieving broadband reflection in the 780–2500 nm near-infrared band, the alternation period, total thickness, and high / low refractive-index film materials of the near-infrared chirped reflective layer can be selected and designed according to conventional methods in the art. Preferably, the near-infrared chirped reflective layer has 5–9 alternation periods, a total thickness of 800–1500 nm, and each period corresponds to a different Bragg wavelength, with its reflection bands forming a tile-like, tightly stacked structure. The high-refractive-index film material A is preferably selected from at least one of titanium dioxide (TiO2), niobium pentoxide (Nb2O5), tantalum pentoxide (Ta2O5), and zirconium oxide (ZrO2), with titanium dioxide (TiO2) being more preferred. The low-refractive-index film material B is preferably silicon dioxide (SiO2) or magnesium fluoride (MgF2), with silicon dioxide (SiO2) being more preferred. All of the above materials are wide-bandgap transparent media with a bandgap greater than 3.1 eV, and can be conventionally selected by those skilled in the art based on target availability and film system design requirements. Titanium dioxide (TiO2) has a bandgap of approximately 3.2 eV and almost zero absorption of visible photons; silicon dioxide (SiO2) is also a wide-bandgap medium. This layer neither absorbs nor reflects in the visible light band (interference caused by the refractive index difference does not constitute a reflection condition in the visible light band)—visible light enters as if there were no film. In the near-infrared band, the refractive index difference between TiO2 and SiO2 (Δn≈1.0) causes the periodic superposition of multi-beam interference to establish a photonic bandgap—near-infrared thermal radiation is firmly blocked. This is the first time that the design concept of "layered functional decoupling" has been precisely executed.

[0018] The conventional approach in existing technologies for decoupled, layered radiation-cooling composite materials involves directly bonding the reflective and emitting layers together or using adhesives. The problem is that any interface with a sudden change in refractive index will produce Fresnel reflection in the visible light band. Even a difference of only 0.06 in refractive index results in approximately 0.04% reflection at each interface. Accumulated reflections at multiple interfaces significantly reduce visible light transmittance. This invention addresses this by incorporating a gradient transition layer between the top layer of the near-infrared chirped reflective layer and the mid-infrared high-emissivity layer. This layer achieves an optically "seamless weld" between the top layer of the near-infrared chirped reflective layer and the mid-infrared high-emissivity layer, allowing for a smooth transition in refractive index between the two functional layers and eliminating all possible interface reflection losses.

[0019] Furthermore, the top layer of the chirped reflective layer is a thick, ultrathin low-refractive-index film layer, closely attached to the high-refractive-index film layer. In the near-field range, the evanescent field of the closely attached high-refractive-index film layer will penetrate the top layer of low-refractive-index film layer, causing its effective refractive index to deviate from the intrinsic refractive index value of the low-refractive-index film layer material B. In this invention, the effective refractive index of the gradient transition layer at its starting side is calibrated and set according to the equivalent interface refractive index calculated from the top-layer parameters of the chirped multilayer film structure. If the gradient transition layer is not calibrated and directly uses the intrinsic refractive index value of the low-refractive-index film layer material B as the starting point of the gradient, then the first few atomic layers of the gradient transition layer will form an anti-reflection step from the intrinsic value of the low-refractive-index film layer material B to the equivalent interface refractive index, which is equivalent to adding a Fresnel reflection source out of thin air to the interface. It is evident that there is a precise coupling constraint between the top optical parameters of the chirped reflective layer and the initial refractive index of the gradient transition layer, which is not recognized by any existing technology. This invention recalibrates the initial refractive index of the gradient transition layer accordingly, so that the chirped reflective layer and the gradient transition layer form an inseparable parameter closed loop.

[0020] Furthermore, the high refractive index film material C is preferably selected from at least one of silicon nitride (Si3N4), aluminum nitride (AlN), and alumina (Al2O3), and more preferably Si3N4. The transparent polymer material D is preferably selected from at least one of polydimethylsiloxane (PDMS), polymethyl methacrylate, polyvinylidene fluoride, and fluorinated ethylene propylene copolymer, and more preferably polydimethylsiloxane (PDMS). The aforementioned polymers are transparent in the visible light band and their molecular bonds are infrared active in the 8–13 μm atmospheric window. In the gradient transition layer, SiO x N y The x-y ratio of the film changes continuously along the thickness direction. The effective refractive index on the starting side is calibrated and set according to the top-layer parameters of the chirped multilayer film structure. On the terminating side, a smooth transition of the refractive index to the PDMS matrix is ​​achieved by introducing polydimethylsiloxane precursor molecules for co-deposition. The total thickness of the gradient transition layer is 200–800 nm, preferably 300–500 nm. The portion of the film layer in which the transparent polymer material D is uniformly doped is the terminal segment, and the thickness of the terminal segment is preferably 10–50 nm.

[0021] The aforementioned layered, functionally decoupled radiation-cooling composite material is based on a multi-component phonon synergistic coverage design for the entire phonon window. The inorganic filler is preferably selected from at least two of the following: silicon dioxide (SiO2), silicon nitride (Si3N4), calcium carbonate (CaCO3), alumina (Al2O3), and zinc oxide (ZnO). These inorganic particles exhibit phonon resonance infrared activity within the 8–13 μm atmospheric window. The fillers can be freely combined, as long as the multi-component phonon resonance peaks form complementary coverage within the 8–13 μm window. The preferred combination of inorganic fillers includes SiO2, Si3N4, and CaCO3. A single type of inorganic filler cannot individually cover the entire 8–13 μm window. The phonon resonance of SiO2 is mainly concentrated around approximately 9 μm (Si–O–Si antisymmetric stretching vibration), and when using SiO2 alone, there is a significant emission gap in the 11–13 μm band. The phonon peak of Si3N4 is located at approximately 10.5–11.5 μm (Si–N bond vibration), while the asymmetric stretching vibration of the C–O bond in CaCO3 falls at approximately 11–13 μm—filling the gap in the long-wavelength band. The phonon resonance peaks of the three fillers form a frequency-complementary "relay coverage" in different sub-intervals within the 8–13 μm window, achieving a combined emission envelope of over 0.93, with no significant emission collapse throughout the window. The thickness of the mid-infrared high-emission layer is preferably 15–50 μm.

[0022] On the other hand, the present invention also provides a method for preparing a layered functionally decoupled radiation-cooling composite material, comprising the following steps:

[0023] S1. Provide a transparent substrate and clean and dry it;

[0024] S2. A near-infrared chirped reflective layer with a chirped multilayer film structure is formed by alternately depositing high-refractive-index and low-refractive-index films on the substrate at a set thickness by magnetron sputtering.

[0025] S3. Using material B and material C as dual target sources, magnetron co-sputtering is performed on the near-infrared chirped reflective layer. According to the preset power gradient curve, the sputtering power of material B is linearly reduced from full power to zero, while the sputtering power of material C is linearly increased from zero to full power. Transparent polymer material D precursor vapor is introduced at the end of sputtering, thereby depositing a gradient transition layer with continuously changing chemical composition and refractive index along the thickness direction.

[0026] S4. On the gradient transition layer, a polymer material D composite slurry containing thermal radiation inorganic functional filler is coated and cured to form a mid-infrared high emission layer.

[0027] In the above-described method for preparing the layered functionally decoupled radiation-cooling composite material, in step S3, the linear slope of the power gradient curve is 0.3–0.8 W / s. The power gradient curve ensures that the component at the deposition initiation side is material B, and the termination side is a material C-rich hybrid state containing organic components.

[0028] The above-mentioned method for preparing a layered functionally decoupled radiation-cooling composite material, wherein the transparent polymer material D is polydimethylsiloxane, and the inorganic filler includes SiO2, Si3N4 and CaCO3;

[0029] The preparation method of the polymer material D composite slurry, namely PDMS composite slurry, is as follows: by mass percentage, 60–78 wt% polydimethylsiloxane, 12–22 wt% silica nanospheres, 5–10 wt% silicon nitride submicron powder, 3–6 wt% calcium carbonate nanoparticles, 1.5–3 wt% silane coupling agent, and 0.05–0.1 wt% platinum catalyst are used as raw materials. The three inorganic functional fillers are pre-treated with silane coupling agent for surface grafting. After diluting the polydimethylsiloxane adhesive with n-hexane to a viscosity of 200–500 mPa·s, the three pre-treated inorganic functional fillers are added sequentially. After dispersion treatment, curing agent and catalyst are added and mixed evenly to prepare polydimethylsiloxane composite slurry.

[0030] While satisfying the requirements for inorganic functional fillers, the dispersion treatment process and parameters can be selected according to conventional methods. In this invention, high-shear dispersion and ultrasonic dispersion processes are preferred, and the specific dispersion treatment parameters can be set according to conventional methods. In addition, the process and parameters for coating the composite slurry in step S4 can also be selected according to conventional methods.

[0031] Furthermore, this invention also provides applications of the above-mentioned composite material in building exterior walls, automobile windows, photovoltaic module encapsulation, agricultural greenhouses, and heat dissipation windows for electronic devices. Specifically, it can be applied in the following ways:

[0032] (I) Energy-efficient architectural glass – from an energy black hole to zero-energy thermal management

[0033] In modern buildings, glass curtain walls contribute 40%–60% of the summer air conditioning cooling load. The composite material provided by this invention, if used in building glass curtain walls, can provide approximately 133W of passive cooling power per square meter under solar irradiance of 127W / m². Based on a 10,000m² curtain wall area, this is equivalent to the non-electric cooling capacity of a 1300kW-class refrigeration unit—at a commercial electricity price of 0.8 yuan per kilowatt-hour, this translates to savings of over 700,000 yuan in electricity costs annually during the 120-day air conditioning season, correspondingly reducing carbon emissions by over 680 tons. If large public buildings such as Beijing Daxing International Airport adopt this material, the annual summer cooling load is expected to be reduced by more than 20%, transforming the massive rooftop glass skylights of the terminal buildings from a "greenhouse effect source" into a "cooling source radiator."

[0034] (II) Automotive Glass – Extending Range, Enhancing Comfort, and Slowing Battery Degradation

[0035] After a car has been exposed to the summer sun, air conditioning can account for 25%–40% of the total energy consumption. The composite material provided by this invention, used in car windows, continuously cools the interior through a transparent radiative cooling mechanism. In summer, actual measurements show that the cabin temperature is more than 8.7°C lower than that of ordinary glass. For an electric SUV with a 72kWh battery pack, the energy savings from cooling will be equivalent to an increase in driving range of 40–60km—an equivalent increase of approximately 40,000km per year. This passive cooling range gain requires no increase in charging frequency or battery hardware upgrades, and has significant value in alleviating "range anxiety" for consumers.

[0036] (III) Photovoltaic Module Packaging

[0037] For every 1°C increase in temperature, the efficiency of crystalline silicon solar cells decreases by approximately 0.4%–0.5%. The composite material provided by this invention, used to integrate a transparent radiative cooler, can reduce the operating temperature of solar cells by approximately 8–12°C, resulting in an absolute efficiency improvement of 0.8–1.2 percentage points. Based on a centralized photovoltaic power station generating 300 million kilowatt-hours of electricity annually, this efficiency improvement translates to an economic return of approximately 18 million yuan.

[0038] (iv) Agricultural greenhouse covering

[0039] In summer, temperatures inside greenhouses often soar above 45°C, severely inhibiting crop growth. Traditional shade nets reduce heat but sacrifice sunlight. The composite material provided by this invention, used for greenhouse roofs, ensures sufficient transmission of photosynthetically active radiation (PAR) while reflecting near-infrared waste heat and radiating heat from inside the greenhouse into space—"cooling without reducing sunlight." Its core significance for large-scale facility agriculture in North China lies in ensuring the germination rate and yield of crops such as tomatoes and peppers under extreme heat waves.

[0040] (v) Transparent heat dissipation windows for electronic devices

[0041] Outdoor LED displays can reach surface temperatures of up to 70°C under intense sunlight. The composite material provided by this invention can reduce the temperature of core components of outdoor electronic devices by about 12°C and extend their service life by about 30%, while not affecting the color gamut and clarity of the display screen—achieving "a visible screen with effective heat dissipation."

[0042] The layered functionally decoupled radiation-cooling composite material and its preparation method provided by this invention have the following beneficial effects:

[0043] (1) The reflective layer of this invention adopts a chirped gradient multilayer film structure with alternating stacks of high-refractive-index and low-refractive-index materials. In the prior art, the use of metal (Ag) reflective layers is very common in the industry, but the risk of corrosion under high temperature and high humidity conditions has been a long-standing problem. According to published research, Ag films begin to corrode after only one day of aging under atmospheric conditions of 60°C and 90% relative humidity, with the corrosion product mainly being Ag2O. Automotive window films are exposed to harsh outdoor environments such as high humidity, salt spray, and acid rain for a long time, and the oxidation failure of the Ag layer will lead to a gradual decline in the reflectivity of the window film year by year—presenting a gradual degradation of "film effectiveness after three years for new cars, light transmittance still present after five years but cooling capacity lost." This invention completely bypasses the metal reflective layer and completes the near-infrared reflection task with a chirped TiO2 / SiO2 all-dielectric multilayer film—the band gap of all dielectric materials is greater than 3.1 eV, and there is no thermodynamic driving force for photochemical oxidation or electrochemical corrosion. Within the foreseeable physical lifespan, there is no degradation problem similar to that of Ag layers. Furthermore, this layer neither absorbs nor reflects light in the visible light band (the interference caused by the refractive index difference does not constitute a reflection condition in the visible light band). In the near-infrared band, the refractive index difference between TiO2 and SiO2 (Δn≈1.0) causes the periodic superposition of multi-beam interference to establish a photonic bandgap, which firmly blocks near-infrared thermal radiation, thus achieving heat blocking without blocking light.

[0044] (2) The present invention sets a gradient transition layer between the near-infrared selective reflective layer and the mid-infrared high emissivity layer. In the prior art, the bonding of the reflective layer and the emissive layer is usually achieved by using a separate adhesive layer. However, the adhesive may undergo interface delamination, yellowing (ultraviolet oxidation decomposition), or water absorption and swelling during long-term use, which not only affects the appearance and light transmittance, but may also lead to optical mismatch between the emissive layer and the reflective layer. The gradient transition layer of the present invention is directly grown on the reflective layer by co-sputtering. There is no organic glue or discontinuity at the interface. The reflective layer, the transition layer, and the emissive layer constitute a continuous refractive index gradient system at the microscopic level, rather than multiple film layers separated by physical interfaces. This allows the two functional layers, the reflective layer and the emissive layer, to have a smooth transition in refractive index. Visible light will not encounter obvious refractive index "steps" throughout the entire process, and the reflection loss is suppressed to almost zero.

[0045] (3) The emission layer of this invention is based on the design concept of multi-component phonon synergistic coverage of the entire window, using SiO2 / Si3N4 / CaCO3 as inorganic functional fillers. The single type of inorganic filler used in the prior art can never cover the entire 8–13 μm window alone. The phonon resonance of SiO2 is mainly concentrated around 9 μm (Si–O–Si antisymmetric stretching vibration), and when SiO2 is used alone, there is a significant emission gap in the 11–13 μm band. The phonon peak of Si3N4 is located at about 10.5–11.5 μm (Si–N bond vibration), and the asymmetric stretching vibration of C–O bond in CaCO3 falls at about 11–13 μm—which fills the gap in the long band. The phonon resonance peaks of the three fillers form a frequency complementary "relay coverage" in different sub-intervals of the 8–13 μm window, with a comprehensive emission envelope of more than 0.93, and no significant emission collapse in the entire window. Through an 8–13 μm atmospheric transparent window, heat from the interior of the covered space is precisely emitted into outer space in the form of infrared radiation, thus achieving passive cooling with zero energy consumption.

[0046] (4) Overall, this composite material is based on the layered functional decoupling design concept and consists of a transparent substrate layer, a near-infrared selective reflective layer, a gradient transition layer, and a mid-infrared high-emissivity layer stacked sequentially. Specifically, the near-infrared reflective layer uses a chirped TiO2 / SiO2 alternating multilayer film to specifically target broadband near-infrared reflection; the mid-infrared emitting layer uses PDMS as a base and three sets of fillers (SiO2 / Si3N4 / CaCO3) to synergistically cover the 8–13 μm atmospheric window; the gradient transition layer uses SiO2... x N y The continuous gradient of components and the refractive index matching precisely coupled with the chirped top-layer parameters completely eliminate interlayer reflection loss. This material achieves comprehensive performance with visible light transmittance ≥88%, near-infrared reflectance ≥85%, atmospheric window emissivity ≥0.93, and haze ≤3%, breaking through the bottleneck of the inability to simultaneously achieve high transparency and efficient cooling in the field of transparent radiative cooling. The preparation method is compatible with the roll-to-roll process route of magnetron sputtering + blade coating, enabling large-scale mass production. It can be used in architectural glass, photovoltaic encapsulation, agricultural greenhouses, and transparent heat dissipation windows for electronic equipment, achieving zero-energy passive cooling with significant energy-saving and carbon-reduction value and commercial significance. Attached Figure Description

[0047] Figure 1 This is a schematic diagram (longitudinal section) of the layered structure of the radiation cooling composite material of the present invention.

[0048] Figure 2 This is a schematic diagram of the multi-component coordinated emission spectrum of the mid-infrared high-emission layer;

[0049] Figure 3 This is a schematic cross-sectional view of the chirped multilayer film structure of the near-infrared selective reflective layer;

[0050] Figure 4 It is the refractive index-thickness relationship curve of the gradient transition layer;

[0051] Figure 5 These are the simulated / measured transmittance and reflectance spectra of the radiation-cooled composite material of this invention in the 300–2500 nm wavelength band;

[0052] Figure 6 The measured emissivity spectrum curves of the radiation cooling composite material of the present invention in the 2.5–25 μm band are shown: a comparison of the measured emission spectra of Example 1, Comparative Example 1, and Comparative Example 2.

[0053] Figure 7 This is a schematic diagram of the process for preparing the radiation-cooled composite material of the present invention. Detailed Implementation

[0054] The technical solutions of various embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are part of the present invention.

[0055] In the following embodiments, the substrate layer is selected from ultra-white float glass or optical-grade PET film.

[0056] For rigid applications, ultra-clear float glass can be commercially available from Xinyi Solar or Flat Glass, with a thickness of 3mm and an iron content (Fe2O3) controlled below 0.01wt%. The ultra-clear glass has a nominal transmittance of ≥91% in the 400–780nm wavelength band. Before use, it must undergo a standard cleaning process: ultrasonically cleaned for 10 minutes each in deionized water (resistivity ≥18.2MΩ·cm), analytical grade acetone (purity ≥99.5%), and anhydrous ethanol (purity ≥99.7%) (ultrasonic frequency 40kHz, power 100W), and then dried with high-purity nitrogen gas (purity ≥99.999%).

[0057] For flexible applications, the optical-grade PET film can be the commercially available Toray Lumirror® U34 series from Japan, with a thickness of 100μm and a visible light transmittance of ≥90%. Before use, the PET film needs to undergo corona treatment to enhance the adhesion of subsequent coatings. The process parameters are a processing power density of 80W·min / m² and a processing speed of 5m / min.

[0058] Example 1

[0059] This embodiment provides a layered functionally decoupled radiation-cooling composite material and its preparation method. For example... Figure 1As shown, the composite material comprises a transparent substrate layer, a near-infrared chirped reflective layer, a gradient transition layer, and a mid-infrared high-emissivity layer stacked sequentially.

[0060] In this embodiment, the substrate is Xinyi ultra-clear float glass, 3mm thick, 300×300mm.

[0061] The near-infrared chirped reflective layer is a chirped multilayer film structure formed by alternating stacks of high-refractive-index TiO2 (anatase phase, refractive index approximately 2.5 at 550 nm) and low-refractive-index SiO2 (amorphous, refractive index approximately 1.46). The thickness of each single layer in each period of the chirped multilayer film structure decreases sequentially along the direction away from the substrate. The first period has the largest TiO2 / SiO2 thickness (approximately 125 / 185 nm), corresponding to the efficient interception of long-wave near-infrared (around ~2 μm); the seventh period has the smallest TiO2 / SiO2 thickness (approximately 60 / 90 nm), corresponding to the precise reflection of short-wave near-infrared (around ~0.8 μm). Each period corresponds to a different Bragg wavelength, and their reflection bands form a tile-like, tightly superimposed structure, creating a wide and flat high-reflectivity barrier across the entire near-infrared band of 780–2500 nm. The chirped reflective layer has 7 alternating periods, with a total thickness of 1630 nm.

[0062] Table 1. Thickness parameter distribution for 7 cycles:

[0063] Periodic number <![CDATA[Thickness of TiO₂ layer (nm)]]> <![CDATA[Thickness of SiO₂ layer (nm)]]> Corresponding Bragg reflection center wavelength (nm) Cycle 1 125 185 ~2020 Cycle 2 115 170 ~1850 3rd cycle 105 155 ~1680 4th cycle 95 140 ~1510 5th cycle 85 125 ~1340 6th cycle 72 108 ~1140 7th cycle 60 90 ~950

[0064] The gradient transition layer comprises a low-refractive-index film material, SiO2 (amorphous, refractive index approximately 1.46), and a high-refractive-index film material, Si3N4 (refractive index approximately 2.0). The chemical composition transitions continuously and gradually along its thickness, with the proportion of SiO2 decreasing and the proportion of Si3N4 increasing. The gradient transition layer also includes polydimethylsiloxane (PDMS), which is uniformly doped into the terminal section of the gradient transition layer to form an organic-inorganic hybrid gradient terminal. This allows the equivalent interface refractive index of the top surface of the near-infrared chirped reflective layer to continuously transition to the effective refractive index of the mid-infrared high-emissivity layer.

[0065] The effective refractive index of the gradient transition layer at its starting side is calibrated and set based on the equivalent interface refractive index calculated from the top-layer parameters of the chirped multilayer film structure. The gradient curve calibration and quality control process is as follows:

[0066] (1) Based on the end period parameters of the chirped reflective layer (TiO2 60 nm / SiO2 90 nm), the equivalent interface refractive index of the top layer of SiO2 was calculated by combining the transfer matrix method (TMM, based on Python tmm package version 0.1.7) and FDTD (Lumerical FDTD Solutions 2024 version). The result is ~1.52.

[0067] (2) Calculate the SiO2 at the starting end of the gradient transition layer based on this value. x N y The x / y stoichiometric ratio was determined to be SiO. 1.8 N 0.1 .

[0068] (3) When the gradient deposition reaches approximately 380 nm, PDMS molecules are introduced to react with SiO in a plasma atmosphere. x N y Co-deposition forms an organic-inorganic hybrid gradient terminator with a thickness of approximately 20 nm. This terminator has an effective refractive index of approximately 1.40, which naturally matches the PDMS matrix (approximately 1.40), achieving a smooth transition of refractive index across materials.

[0069] (4) The refractive index profile of the film needs to be modeled and verified by a spectroscopic ellipsometer (JA Woollam M-2000, wavelength range 245–1690nm): The measured Ψ and Δ data are modeled using a three-layer gradient model (bottom SiO2). 1.8 N 0.1 →Middle SiO x N y (Continuous variation → top hybrid) Fitting, MSE value ≤ 15 is considered qualified.

[0070] Table 2. Refractive index gradient profile parameters (along the film thickness direction)

[0071] Distance from bottom (nm) <![CDATA[Component state w(SiO2) wt%]]> Refractive index n (550nm) Extinction coefficient k (550nm) 0 <![CDATA[~98%SiO2]]> 1.52 <0.0001 100 <![CDATA[~75%SiO2]]> 1.56 <0.0001 200 <![CDATA[~50%SiO2]]> 1.66 <0.0001 300 <![CDATA[~25%SiO2]]> 1.82 <0.0001 380 <![CDATA[Si3N4-rich]]> ~2.0 <0.0001 400 (top) <![CDATA[SiO x N y -PDMS hybridization]]> ~1.40 <0.0001

[0072] The mid-infrared high-emissivity layer comprises polydimethylsiloxane (PDMS) and uniformly dispersed thermally radiating inorganic functional fillers SiO2, Si3N4, and CaCO3. For example... Figure 2 As shown, the phonon resonance of SiO2 is mainly concentrated around 9 μm (Si–O–Si antisymmetric stretching vibration); the phonon peak of Si3N4 is located at about 10.5–11.5 μm (Si–N bond vibration); and the asymmetric stretching vibration of C–O bond in CaCO3 falls at about 11–13 μm. The phonon resonance peaks of the three fillers form a frequency complementary “relay coverage” in different sub-intervals of the 8–13 μm window, forming a broadband emission envelope with a comprehensive emission envelope of more than 0.93 in the 8–13 μm atmospheric window, and there is no obvious emission collapse in the entire window.

[0073] This embodiment also provides a method for preparing the above-mentioned layered functionally decoupled radiation cooling composite material. In the following preparation method, the substrate is Xinyi ultra-white float glass (3mm thick, 300×300mm). The TiO2 target material is a high-purity TiO2 ceramic target from ZNXC®, with a purity ≥99.99%, a density ≥95% of the theoretical density, a diameter of 3 inches (76.2mm), and a thickness of 6mm. The SiO2 target material is a high-purity SiO2 target from the same brand, with a purity ≥99.99%, a density ≥90% of the theoretical density, and the same specifications. The growth rate is approximately 0.25nm / s at a power of 200W; the SiO2 growth rate is approximately 0.35nm / s at a power of 180W. The Si3N4 target used is a high-purity Si3N4 ceramic target from ZNXC®, with a purity ≥99.9%, a density ≥92% of the theoretical density, a diameter of 3 inches (76.2 mm), a thickness of 6 mm, and a growth rate of approximately 0.3 nm / s at a power of 200 W.

[0074] The preparation method specifically includes the following steps:

[0075] S1. The substrate was sequentially ultrasonically cleaned with deionized water, acetone, and anhydrous ethanol for 10 minutes each, with an ultrasonic frequency of 40 kHz and a power of 100 W. After being dried with high-purity nitrogen, it was placed into the magnetron sputtering vacuum chamber.

[0076] S2. TiO2 and SiO2 layers are deposited alternately on the substrate by magnetron sputtering according to the thicknesses shown in Table 1 to form a near-infrared chirped reflective layer with a chirped multilayer film structure.

[0077] The specific parameters of the magnetron sputtering process are as follows: Sputtering method: Radio frequency (RF) magnetron sputtering, power supply frequency 13.56MHz; Sputtering atmosphere and gas parameters: High-purity Ar (purity ≥99.999%) is introduced during TiO2 target sputtering, Ar flow rate 30 sccm; During SiO2 target sputtering, Ar flow rate 25 sccm, O2 flow rate 2 sccm (trace oxygen to compensate for possible oxygen deficiency in SiO2 during deposition); Working pressure: 0.5Pa, controlled in a closed loop by a mass flow controller (MFC) and a throttle valve (MFC accuracy ±1% of full scale); Target-substrate distance: 80mm; Sputtering power and rate: TiO2 target 200W, deposition rate approximately 0.25nm / s; SiO2 target 180W, deposition rate approximately 0.35nm / s; Substrate temperature: Room temperature to 100°C (no active heating, temperature rise due to self-heating during deposition does not exceed 100°C); Base vacuum: ≤5×10⁻ 4Pa; Film thickness control and uniformity: The thickness of each layer was precisely controlled by sputtering time—the sputtering time for the TiO2 layer was gradually reduced from 500s (125nm) to 240s (60nm); the sputtering time for the SiO2 layer was gradually reduced from 529s (185nm) to 257s (90nm), with a total sputtering time of approximately 54 minutes. The substrate was rotated at a uniform speed (10rpm), and the in-situ monitoring was performed using a German SENTECH Instruments SE800PV laser ellipsometer, with an in-plane thickness deviation of ≤±3%.

[0078] To optimize the performance of the prepared radiation-cooled composite material, the following operational precautions should be taken in addition to the general magnetron sputtering process:

[0079] (1) Strict control of oxygen partial pressure. If the oxygen partial pressure is too low during TiO2 sputtering, non-stoichiometric TiO2 will be generated. 2-x (Oxygen vacancy defects) introduce light-colored centers—the membrane layer appears slightly yellowish-brown to the naked eye, directly impairing visible light transmittance. It is recommended to use a residual gas analyzer (RGA) to monitor the oxygen partial pressure within the chamber and to calibrate the MFC periodically.

[0080] (2) Target surface cooling management. After each layer is deposited, the sputtering power supply is paused for 10 seconds to allow the target surface to dissipate heat and cool down. Continuous full-power sputtering will cause the local temperature of the target material to be too high - the sputtering rate drift and the risk of target surface cracking will increase significantly, which will affect the film thickness accuracy and batch consistency.

[0081] (3) Ensuring substrate rotation uniformity. The substrate holder rotates at a constant speed of 10 rpm during sputtering to ensure uniform film thickness over a large area. If the rotation stops, the film thickness will exhibit a non-uniform distribution in the in-plane that depends on the target source position, which may lead to deviations in the transmittance and reflectance of the finished window film at different locations.

[0082] (4) Cleanliness. Before the sputtering chamber is put into use, the chamber walls should be cleaned with high-purity Ar plasma for 5 minutes (power 150W, pressure 2.0Pa) to remove as much water vapor and organic residue as possible adsorbed on the chamber wall surface. If the target surface is contaminated, it should be gently polished with fine sandpaper (grit ≤1200 mesh) until it is shiny, and then wiped clean with anhydrous ethanol to ensure that the sputtering process is stable and free from abnormal discharge.

[0083] S3. Using SiO2 and Si3N4 targets as dual target sources, magnetron co-sputtering is performed on the near-infrared chirped reflective layer. The sputtering power of the two targets varies along the time axis according to a preset curve: initially, the SiO2 target power is 200W and the Si3N4 target power is 0W; in the following approximately 400 seconds, the SiO2 target power linearly decreases to 0W, while the Si3N4 target power linearly increases to 200W. The linear slope of the power gradient is 0.5W / s. Deposition atmosphere and gas parameters: high-purity Ar 30 sccm, trace amount of N 25 sccm (to compensate for nitrogen loss during Si3N4 deposition and maintain the stability of the Si:N stoichiometric ratio), working pressure 0.5 Pa. The overall deposition rate is approximately 0.3–0.5 nm / s. At 380 nm, PDMS precursor vapor (Sylgard™ 184 base gel) that volatilizes at 80°C is introduced through the gas inlet at a flow rate of approximately 0.1 sccm, allowing PDMS molecules to react with SiO in the plasma atmosphere. x N y Co-deposition forms an organic-inorganic hybrid gradient terminal with a thickness of approximately 20 nm, with a final thickness of 400 nm.

[0084] To optimize the performance of the prepared radiation-cooled composite material, the following operational precautions should be taken in addition to the general magnetron sputtering process:

[0085] (1) Power Gradient Linearity. The linearity of the power gradient curve is the most critical process parameter in this step. Any power fluctuation (such as arc discharge or instantaneous drift caused by target poisoning) will cause the refractive index distribution to become "stepped" rather than continuously gradient—this is equivalent to artificially introducing multiple tiny refractive index steps inside the gradient layer, which not only fails to eliminate reflection but also increases the scattering sources. It is recommended to use a sputtering power supply with closed-loop power feedback control (such as the Cesar®133 RF power supply from AE (Advanced Energy), with power control accuracy better than ±1W), and to test-deposit a single layer of SiO on a clean glass slide using the same gradient procedure before wafer ejection. x N y The film was only fully integrated into the device after its optical constants were verified using an ellipsometer.

[0086] (2) Cross-contamination control of the target surface. During dual-target co-sputtering, the SiO2 target may be contaminated by sputtered Si3N4 particles, and vice versa. It is advisable to install a physical isolation baffle (dark area shield) between the two targets, and to perform target surface cleaning sputtering every few batches (sputtering the target surface for 2-3 minutes under pure Ar atmosphere to remove the contamination layer) to ensure the long-term repeatability of the graded layer composition curve.

[0087] (3) Precision of PDMS precursor vapor flow rate. Fluctuations in PDMS vapor flow rate will cause the refractive index endpoint of the top hybridization region to drift. If the vapor flow rate is too high, a large number of PDMS molecules may be adsorbed on the sputtering chamber wall, becoming subsequent sputtering particles—leading to batch-to-batch cross-contamination. It is recommended to install a liquid nitrogen cold trap between the vapor inlet pipe and the sputtering chamber to precisely control the vapor transfer rate and intercept excess organic molecules.

[0088] S4. On the gradient transition layer, a PDMS composite slurry containing thermal radiation inorganic functional fillers SiO2, Si3N4 and CaCO3 is coated and cured to form a mid-infrared high emission layer.

[0089] In step S4, the PDMS composite slurry is prepared in-house, and the specific method is as follows.

[0090] Table 3. Composition of PDMS composite slurry formulation (based on 100g total solids mass)

[0091] Components Mass (g) Percentage by weight (wt%) Brand / Model Particle size / specification Function PDMS-based adhesive 70.00 70.00% Dow Corning Sylgard™ 184 Viscosity approximately 5000 mPa·s Transparent flexible substrate, Si–O bonds intrinsically provide infrared emission <![CDATA[SiO₂ nanospheres]]> 16.00 16.00% Sigma-Aldrich 718483 Particle size 200±20nm Phonon resonance enhances emission in the 9μm region <![CDATA[Large-particle-size SiO₂ spheres]]> 2.00 2.00% Nissan Chemical Snowtex® ST-ZL Particle size 100–150 nm Supplementing short-range launches and increasing particle packing density <![CDATA[Si3N4 submicron powder]]> 6.00 6.00% UBE (Ube Industries) SN-E10 Particle size approximately 500 nm Phonon resonance enhances emission at 10.5–11.5 μm. <![CDATA[CaCO₃ nanoparticles]]> 4.00 4.00% Solvay Socal® 312 Particle size approximately 80nm C–O bond vibration enhances 11–13 μm emission. Silane coupling agent 1.90 1.90% Evonik Dynasylan® GLYMO (KH-560) Liquid, with ≥97% active ingredient. Enhance the interfacial bonding between inorganic fillers and PDMS Platinum catalyst 0.10 0.10% Dow Corning Sylgard™ 184 Kit Platinum content approximately 1% Catalytic PDMS crosslinking and curing PDMS curing agent 7.00 — (Base adhesive: curing agent = 10:1) Same as above — Crosslinking agent

[0092] Before being mixed with PDMS, the three types of inorganic functional fillers undergo surface grafting pretreatment with a silane coupling agent, which effectively ensures the long-term stability and film uniformity of the composite slurry. The filler surface pretreatment process is as follows:

[0093] S411. Prepare the coupling agent solution: KH-560 (GLYMO) 5g, anhydrous ethanol 95g, deionized water 5g (ratio of ethanol:water = 95:5v / v, total solution volume 100mL). Stir at 300rpm for 10min on a magnetic stirrer to fully hydrolyze the coupling agent.

[0094] S412. Pretreatment: SiO2 nanospheres (18g), Si3N4 submicron powder (6g), and CaCO3 nanoparticles (4g) are respectively immersed in the above coupling agent solution and magnetically stirred in a 40°C water bath for 2 hours to allow the silane coupling agent molecules to undergo a condensation grafting reaction with the hydroxyl groups on the filler surface.

[0095] S413. After pretreatment, the packing material is separated by centrifugation at 8000 rpm for 10 min. It is then washed three times with anhydrous ethanol to remove unreacted coupling agent and byproducts. Finally, it is dried in a vacuum oven at 60°C for 2 hours (pressure ≤0.01MPa) and sealed for later use.

[0096] The preparation process of PDMS composite slurry includes the following steps:

[0097] S421. Diluting the Base Adhesive: Weigh 70g of Sylgard™ 184 PDMS base adhesive into a clean 250mL tall glass beaker, and add 30mL of n-hexane (analytical grade, boiling point 69°C, water content ≤0.01%) as a volatile diluent. Stir with a mechanical stir bar at 300rpm for 10min until the base adhesive is completely dissolved. Hexane dilution reduces the system viscosity from approximately 5000mPa·s to approximately 350mPa·s. This reduced system viscosity ensures that subsequent high-shear dispersion effectively breaks up filler agglomerates, as shear force transmission efficiency is significantly reduced in high-viscosity media, making it impossible to break up micron-sized agglomerates.

[0098] S422. Filler addition and mixing: With continuous stirring, the three pretreated inorganic fillers are slowly added to the PDMS dilution solution while stirring. During the addition process, the stirring speed is maintained at ≥500 rpm to ensure that the powder is uniformly suspended in the solution.

[0099] S423, High Shear Dispersion: After all filler has been added, transfer the mixture to a high-speed shear disperser (IKA T25digital ULTRA-TURRAX®, equipped with S25N-25G dispersing head) and shear disperse at 11,000 rpm for 15 minutes. The strong hydraulic shear force "tears" the filler clumps into individual or extremely small aggregates, uniformly dispersing them within the PDMS matrix. The dispersed slurry should be a uniform white suspension, without obvious sediment or large particles—if these are clearly visible, it indicates insufficient pre-dispersion, requiring replacement with a high-energy ball mill or extended ultrasonic time.

[0100] S424. Ultrasonic Dispersion: The dispersed slurry is placed in an ice-water bath and ultrasonically dispersed for 30 minutes using a probe-type ultrasonic instrument (ultrasonic power 200W, frequency 40kHz, pulse mode: 5 seconds working + 2 seconds intermittent). Ice-water bath cooling prevents temperature rise that could lead to hexane boiling and premature PDMS crosslinking. After ultrasonication, the slurry should be a uniform suspension with no obvious particle sedimentation.

[0101] S425. Add curing agent and catalyst. Add 7g of Sylgard™ 184 curing agent and 0.10g of platinum catalyst at a mass ratio of base adhesive to curing agent of 10:1. Stir at 500rpm for 5min to mix evenly and prepare PDMS composite slurry for later use.

[0102] The blade coating film formation process includes the following steps:

[0103] S431. The prepared PDMS composite slurry is smoothly poured onto one end of the substrate surface of the deposited gradient transition layer to form a uniform slurry pool.

[0104] S432. Using an automatic doctor blade coater (ZEHNTNER ZAA 2300, blade length is film width + 20mm allowance), set the blade gap to 60μm (corresponding to wet film thickness), and coat the film at a constant speed of 15mm / s along the film surface.

[0105] S433. After the coating is completed, the sample is left to stand at room temperature (22°C) for 20 minutes to level. During this period, hexane begins to evaporate from the film surface, and the film surface automatically flattens under the drive of surface tension, eliminating the doctor blade texture; some low-boiling-point solvents also escape from the film.

[0106] S434. Gently transfer the sample into a forced-air drying oven. Pre-curing at 60°C for 30 minutes allows the PDMS molecular chains to initially cross-link and form, fixing the film morphology and preventing bubbling caused by direct high-temperature curing. Then, raise the temperature to 90°C for main curing for 2 hours to ensure the cross-linking reaction is fully completed and the hexane and coupling reaction byproducts are completely volatilized. The heating rate should be controlled at 2°C / min to avoid excessively rapid heating that could cause pore defects on the film surface.

[0107] S435. After curing, allow to cool naturally to room temperature at a rate of approximately 1°C / min. The resulting mid-infrared high-emissivity dry film thickness is approximately 30 μm. The thickness can be flexibly adjusted by the doctor blade gap and the solid content of the slurry, ranging from 15 to 50 μm.

[0108] To optimize the performance of the prepared radiation-cooling composite material, the blade coating process should be carried out under the following environmental conditions: the entire process of blade coating, static leveling, and curing should be conducted in a cleanroom (ISO Class 7 or higher, i.e., no more than 352,000 particles ≥0.5μm per cubic meter of air), at a temperature of 22±2°C and a relative humidity of 40±5%. Excessive humidity will cause microbubbles to form during PDMS curing (water vapor and trace amounts of hydrogen released from the crosslinking reaction combine to form pores), leading to decreased film transparency and increased haze. Insufficient humidity will cause hexane to evaporate too quickly, potentially resulting in an "orange peel" texture or excessive surface roughness.

[0109] The measured properties of the radiation-cooling composite material prepared in this embodiment are shown in Table 4:

[0110] Table 4 Measured values ​​of the properties of radiation-cooled composite materials

[0111] Performance parameters Target value of the present invention Measured values ​​in Example 1 Measurement standards / equipment Average transmittance of visible light (400–780 nm) ≥88% 89.2% Spectrophotometer (PerkinElmer Lambda 1050+ with 150mm integrating sphere), conforming to ISO 9050 / GB / T 2680 Near-infrared average reflectance (780–2500 nm) ≥85% 86.5% Same as above Average emissivity of atmospheric window (8–13 μm) ≥0.93 0.94 FTIR spectrometer (Bruker VERTEX 70V with A562 integrating sphere + liquid nitrogen-cooled MCT detector) Haze ≤3% 2.3% ASTM D1003, BYK-Gardner haze-gard i Outdoor temperature drop (AM1.5, ambient 25°C) ≥8.5°C 8.7°C lower than bare glass substrate K-type thermocouple + data logger (Agilent 34970A), Beijing sunny weather, irradiance ~800W / m², ambient temperature 26.5°C Net cooling power (AM1.5, ambient 25°C) ≥120W / m² Approximately 133W / m² Calculation based on spectral data and thermal balance model Flexibility (only flexible version, no gradient top layer) Bending radius ≤10mm \ 10mm cylinder bending test 100 times

[0112] The present invention is systematically compared with the physical parameters of mainstream global radiative cooling products and representative academic solutions from multiple dimensions. The specific data are shown in Table 5.

[0113] As can be seen from Table 5:

[0114] (1) All-dielectric structure and metal-containing reflection: The use of Ag reflective layers is very common in the industry—high reflectivity and mature technology, but its corrosion risk under high temperature and humidity conditions has been a long-standing problem. According to published research, Ag films begin to corrode after only one day of aging under atmospheric conditions of 60°C and 90% relative humidity, with the main corrosion product being Ag2O. Automotive window films are exposed to harsh outdoor environments such as high humidity, salt spray, and acid rain for a long time, and the oxidation failure of the Ag layer will lead to a gradual decline in the reflectivity of the window film—presenting a gradual degradation of "film effectiveness after three years for new cars, light transmittance still present after five years but cooling capacity lost." This invention completely bypasses the metal reflective layer and completes the near-infrared reflection task with a chirped TiO2 / SiO2 all-dielectric multilayer film—the band gap of all dielectric materials is greater than 3.1 eV, and there is no thermodynamic driving force for photochemical oxidation or electrochemical corrosion. Within the foreseeable physical lifespan, there is no degradation problem similar to that of Ag layers.

[0115] (2) "Gradual transition" and "adhesive / physical bonding": CN120735376B discloses a high-power radiation cooling film and its preparation method, which uses an independent adhesive layer to achieve bonding between the reflective layer and the emitting layer. However, the adhesive may experience interfacial delamination, yellowing (UV oxidation decomposition), or water absorption and swelling during long-term use, which not only affects the appearance and light transmittance, but may also lead to optical mismatch between the emitting layer and the reflective layer—a weak link in the integrated performance. The gradient transition layer of the present invention is directly grown on top of the reflective layer by co-sputtering, and there is no organic glue or discontinuity at the interface—the reflective layer, transition layer, and emitting layer constitute a continuous refractive index gradient system at the microscopic level, rather than multiple film layers separated by a physical interface.

[0116] (3) Uniqueness of "High Performance + Transparency Integration": Among all the comparative technical solutions, only the present invention can achieve near-infrared reflectivity ≥85% and atmospheric window emissivity ≥0.93 at the same time under the premise of visible light transmittance ≥88%. SkyCoolSystems' products are typical reflective high-power solutions with almost zero visible light transmittance; MIT / SNU's whole vehicle test solution only achieved >70% visible light transmittance, which is about 18 percentage points lower than the ≥88% of the present invention, which directly determines whether the window film can be made so that the occupants cannot feel the existence of the film at all; Beihang's photonic crystal solution focuses on wide transmittance in the visible light band; existing architectural heat insulation films (such as 3M Prestige series) and automotive window films (such as 3MCrystalline series) on the market have a clear technological gap in mid-infrared emissivity.

[0117] Table 5. Comparison of this invention with mainstream global radiative cooling products and representative academic solutions.

[0118]

[0119] Comparative Example 1

[0120] Compared to Example 1, this comparative example uses a single-component SiO2 emitter layer. The emitter layer formulation is: 80g PDMS + 20g SiO2 nanospheres (Sigma-Aldrich 718483) (20wt%), without the addition of Si3N4 and CaCO3. The remaining structure and process are exactly the same as in Example 1.

[0121] Measured properties of the composite material prepared in Comparative Example 1:

[0122] Average emissivity in the 8–13 μm band: 0.86; with the emissivity in the 11–13 μm sub-band being only about 0.72.

[0123] Outdoor temperature reduction: 4.2°C lower than bare glass substrate.

[0124] While the single SiO2 scheme exhibits considerable emissivity near 9 μm, it suffers from a significant emission gap in the long-wavelength range of 11–13 μm, which is an inherent physical limitation of SiO2 phonon resonance. The three-component synergistic strategy of this invention precisely solves this "long-wavelength depression" problem. The C–O bond vibration of CaCO3 (~11–13 μm) fills the gap in long-wavelength emission of SiO2 and Si3N4.

[0125] Comparative Example 2

[0126] Compared to Example 1, the emitter layer in this comparative example uses a two-component SiO2 + Si3N4. The emitter layer formulation is: 70g PDMS + 18g SiO2 (Sigma-Aldrich 718483) + 8g Si3N4 (UBE SN-E10) (same ratio as Example 1, but without CaCO3). The remaining structure and process are completely the same as in Example 1.

[0127] Measured properties of the composite material prepared in Comparative Example 2:

[0128] Average emissivity in the 8–13 μm band: 0.90; however, the emissivity in the 11.5–13 μm band remains relatively low: approximately 0.78.

[0129] Outdoor temperature drop: 2.3°C lower than in Example 1.

[0130] While the two-component system shows improvement over single-SiO2, the long-wavelength "gap" of 11.5–13 μm remains unfilled—this is precisely where CaCO3's unique phonon frequency contribution lies. The leap in the synergistic emissivity of the three components is not a simple linear superposition of the emissivity of any single-component or two-component scheme, but rather a systematic gain resulting from the precise splicing of different phonon frequencies—this "1+1+1>3" effect, which goes beyond simple addition, constitutes a powerful support for the inventiveness of the emitter layer in this invention.

[0131] Comparative Example 3

[0132] Compared to Example 1, this comparative example uses a periodic reflective layer of equal thickness without a gradient transition layer. The specific structure consists of a substrate, a 7-period TiO2 / SiO2 reflective layer of equal thickness, and a mid-infrared high-emissivity layer, arranged sequentially. The emissive layer is directly coated onto the reflective layer, with each period of the reflective layer containing 100nm of TiO2 and 140nm of SiO2, for the same total thickness as in Example 1. All other materials, structures, and processes are identical to those in Example 1.

[0133] Measured properties of the composite material prepared in Comparative Example 3:

[0134] Visible light transmittance: 83.5%, a decrease of approximately 5.7 percentage points compared to Example 1;

[0135] Near-infrared reflectance: 78%, a decrease of approximately 8.5 percentage points compared to Example 1; the equal thickness design cannot cover the entire near-infrared band.

[0136] Haze: 4.5%, which is about 2.2 percentage points higher than in Example 1, indicating that there are indeed additional reflections and small scattering sources at the interface without a gradient transition layer.

[0137] The two changes in Comparative Example 3—removing the gradient transition layer and reducing the chirped reflective layer to a uniform thickness—resulted in a sharp drop in visible light transmittance of nearly 6 percentage points. This magnitude is far greater than the commonly accepted explanation of a 0.06 refractive index difference interface producing ~0.04% reflection, confirming the irreplaceable comprehensive effect of the gradient transition layer in suppressing accumulated Fresnel reflection at multi-layer interfaces. The near-infrared reflectance plummeted from 86.5% to 78%, validating the bandwidth expansion contribution of the chirped design, i.e., a uniform thickness period cannot form a continuous reflection band from 0.8–2.5 μm.

[0138] Comparative Example 4

[0139] This comparative example uses a conventional transparent window film containing an Ag reflective layer to exemplify the present invention.

[0140] A commercially available Ag-containing low-emissivity (Low-E) window film sample, 3M Crystalline CR 70®, with a nominal visible light transmittance of approximately 70%, was used for an outdoor cooling comparison test under the same conditions.

[0141] Measured performance values ​​of Ag-containing low-emissivity (Low-E) window film samples:

[0142] Visible light transmittance: approximately 70%, significantly lower than the 89.2% of this invention;

[0143] Outdoor temperature reduction: 2.8°C lower than bare glass substrate, far less than 8.7°C in Example 1, a difference of nearly 6°C.

[0144] Silver-containing Low-E films primarily rely on reflecting solar radiation for passive heat insulation. However, their mid-infrared emissivity in the 8–13 μm atmospheric window is only about 0.85, making it unable to effectively radiate heat into space. This means the heat is "blocked but not dissipated," ultimately failing to achieve a significant temperature reduction below ambient levels. In contrast, this invention achieves highly efficient heat dissipation through a three-component synergistic emissive layer, which is the source of its overwhelming advantage in terms of cooling magnitude.

[0145] Example 2: Transparent Radiation Cooling Composite Film for Flexible Automotive Sunroofs

[0146] Compared to Example 1, this embodiment differs only in that the substrate layer is replaced with a 100μm PET film (Toray Lumirror® U34) that has undergone corona treatment. During sputtering, the substrate temperature is controlled below 60°C to prevent thermal deformation and crystallization of the PET. The gap between the emitter layer coatings is reduced to 40μm, resulting in a dry film thickness of approximately 20μm to ensure flexibility. The remaining structure and process steps are consistent with the previous embodiment.

[0147] The measured properties of the composite material prepared in this embodiment are as follows:

[0148] Visible light transmittance: 88.5%;

[0149] Emissivity of 8–13 μm: 0.93;

[0150] After 100 bends at a 10mm curvature, the transmittance retention rate is >97%, with no visible cracks or delamination.

[0151] Under conditions of a sealed model box (40×40×40cm acrylic box with embedded K-type thermocouple) and a solar irradiance of 850W / m², the internal temperature was 9.3°C lower than that of the control group with ordinary PET window film.

[0152] Example 3

[0153] In this embodiment, the composite material provided in Example 1 is used to encapsulate the photovoltaic module. Outdoor testing (ambient temperature 40°C): the operating temperature of the monocrystalline silicon photovoltaic module is 8–12°C lower than that of conventional encapsulation glass, and the absolute photoelectric conversion efficiency is improved by 0.8–1.2 percentage points.

[0154] The above embodiments and comparative examples fully demonstrate the rigor of the present invention in terms of composition and structure, its outstanding advantages in spectral performance, and its reproducible process reliability.

[0155] Those skilled in the art will recognize that the embodiments described herein are intended to help the reader understand the principles of the invention, and should be understood that the scope of protection of the invention is not limited to such specific statements and embodiments. Those skilled in the art can make various other specific modifications and combinations based on the technical teachings disclosed in this invention without departing from the spirit of the invention, and these modifications and combinations are still within the scope of protection of this invention.

Claims

1. A layered functionally decoupled radiation-cooling composite material, characterized in that: It includes a transparent substrate layer, a near-infrared chirped reflective layer, a gradient transition layer, and a mid-infrared high-emissivity layer stacked sequentially. The near-infrared chirped reflective layer is a chirped multilayer film structure formed by alternating stacks of high-refractive-index film material A and low-refractive-index film material B, wherein the refractive index of the high-refractive-index film material A is n. A The refractive index of the low refractive index film material B is n. B ; The gradient transition layer comprises a low-refractive-index film material B and a high-refractive-index film material C, with a continuous gradient in chemical composition along its thickness direction. The content ratio of the low-refractive-index film material B decreases, while the content ratio of the high-refractive-index film material C increases. The refractive index of the high-refractive-index film material C is n. C n B <n C <n A ; The mid-infrared high-emissivity layer includes a transparent polymer material D and a thermally radiative inorganic functional filler uniformly dispersed within it. The gradient transition layer also includes a transparent polymer material D, which is uniformly doped into the terminal section of the gradient transition layer to form an organic-inorganic hybrid gradient terminal. The near-infrared chirped reflective layer is used to form broadband reflection in the 780–2500 nm near-infrared band. The gradient transition layer is used to continuously transition the equivalent interface refractive index of the top surface of the near-infrared chirped reflective layer to the effective refractive index of the mid-infrared high-emissivity layer to eliminate interlayer interface Fresnel reflection loss. The mid-infrared high-emissivity layer is used to form broadband emission in the 8–13 μm atmospheric window.

2. The layered functionally decoupled radiation cooling composite material according to claim 1, characterized in that: The thickness of a single layer in the near-infrared chirped reflective layer decreases periodically along the direction away from the substrate in each cycle of the chirped multilayer film structure, so that the Bragg reflection wavelength corresponding to the bottom cycle is located in the long-wave near-infrared range and the Bragg reflection wavelength corresponding to the top cycle is located in the short-wave near-infrared range.

3. The layered functionally decoupled radiation cooling composite material according to claim 1, characterized in that: The effective refractive index of the gradient transition layer on its starting side is calibrated and set according to the equivalent interface refractive index calculated from the top-layer parameters of the chirped multilayer film structure.

4. The layered functionally decoupled radiation cooling composite material according to claim 1, characterized in that: The transparent polymer material D is selected from at least one of polydimethylsiloxane, polymethyl methacrylate, polyvinylidene fluoride, and fluorinated ethylene propylene copolymer; the thermal radiation inorganic functional filler is selected from at least two of SiO2, Si3N4, CaCO3, Al2O3, and ZnO; the high refractive index film material A is selected from at least one of TiO2, Nb2O5, Ta2O5, and ZrO2; the low refractive index film material B is SiO2 or MgF2; and the high refractive index film material C is selected from at least one of Si3N4, AlN, and Al2O3.

5. The layered functionally decoupled radiation cooling composite material according to claim 1, characterized in that: The near-infrared chirped reflective layer has 5–9 alternating periods and a total thickness of 800–1500 nm. Each period corresponds to a different Bragg wavelength, and its reflective bands are tightly superimposed in a tile-like manner.

6. The layered functionally decoupled radiation cooling composite material according to claim 1, characterized in that: The total thickness of the gradient transition layer is 200–800 nm, and the thickness of the terminal segment is 10–50 nm.

7. A method for preparing a layered functionally decoupled radiation-cooling composite material according to any one of claims 1-6, characterized in that: Includes the following steps: S1. Provide a transparent substrate and clean and dry it; S2. A near-infrared chirped reflective layer with a chirped multilayer film structure is formed by alternately depositing high-refractive-index and low-refractive-index films on the substrate at a set thickness by magnetron sputtering. S3. Using material B and material C as dual target sources, magnetron co-sputtering is performed on the near-infrared chirped reflective layer. According to the preset power gradient curve, the sputtering power of material B is linearly reduced from full power to zero, while the sputtering power of material C is linearly increased from zero to full power. Transparent polymer material D precursor vapor is introduced at the end of sputtering, thereby depositing a gradient transition layer with continuously changing chemical composition and refractive index along the thickness direction. S4. On the gradient transition layer, a polymer material D composite slurry containing thermal radiation inorganic functional filler is coated and cured to form a mid-infrared high emission layer.

8. The method for preparing the layered functionally decoupled radiation-cooling composite material according to claim 7, characterized in that: In step S3, the linear slope of the power gradient curve is 0.3–0.8 W / s.

9. The method for preparing the layered functionally decoupled radiation-cooling composite material according to claim 7, characterized in that: The transparent polymer material D is polydimethylsiloxane, and the inorganic filler includes SiO2, Si3N4 and CaCO3. The preparation method of the polymer material D composite slurry, namely polydimethylsiloxane composite slurry, is as follows: 60–78 wt% polydimethylsiloxane matrix, 12–22 wt% silica nanospheres, 5–10 wt% silicon nitride submicron powder, 3–6 wt% calcium carbonate nanoparticles, 1.5–3 wt% silane coupling agent, and 0.05–0.1 wt% platinum catalyst are used as raw materials. The three inorganic functional fillers are pre-treated with silane coupling agent for surface grafting. After diluting the polydimethylsiloxane adhesive with n-hexane to a viscosity of 200–500 mPa·s, the three pre-treated inorganic functional fillers are added sequentially. After dispersion treatment, the curing agent and catalyst are added and mixed evenly to prepare the polydimethylsiloxane composite slurry.

10. The application of the composite material as described in any one of claims 1-6 in building exterior walls, automobile windows, photovoltaic module encapsulation, agricultural greenhouses, and heat dissipation windows for electronic devices.

Citation Information

Patent Citations

  • A high-power radiative cooling film and a method of making the same

    CN120735376B